Engineering students' conceptions of the derivative and some implications for their mathematical education - Bingolbali, E.; Monaghan, J.; Roper, T. (Taylor & Francis Ltd, 2007)
This paper explores Mechanical Engineering students' conceptions of and preferences for conceptions of the derivative, and their views on mathematics. Data comes from pre-, post-and delayed post-tests, a preference test, interviews with students and an analysis of calculus courses. Data from Mathematics students is used to make comparisons with Mechanical Engineering students. The results show that Mechanical Engineering students' conceptions of and preferences for the derivative develop in the direction of the rate of change aspects while those of Mathematics students develop in the direction of tangent aspects, and that Mechanical Engineering students view mathematics as a tool and want the application aspects in their course. Students' developing conceptions, preferences and views with regard to teaching and departmental affiliation are considered and educational implications are suggested for the mathematical education of engineering students.